Segregation of PIP2 and PIP3 into distinct nanoscale regions within the plasma membrane - Jie Wang; David A. Richards (Biology Open, 2012)
Summary PIP2 and PIP3 are implicated in a wide variety of cellular signaling pathways at the plasma membrane. We have used STORM imaging to localize clusters of PIP2 and PIP3 to distinct nanoscale regions within the plasma membrane of PC12 cells. With anti-phospholipid antibodies directly conjugated with AlexaFluor 647, we found that PIP2 clusters in membrane domains of 64.5±27.558 nm, while PIP3 clusters had a size of 125.6±22.408 nm. With two color direct STORM imaging we show that >99% of phospholipid clusters have only one or other phospholipid present. These results indicate that lipid nano-domains can be readily identified using super-resolution imaging techniques, and that the lipid composition and size of clusters is tightly regulated.